EFEKTIVITAS PEMUNGUTAN PAJAK KENDARAAN BERMOTOR DALAM RANGKA MENINGKATKAN PENERIMAAN PAJAK DAERAH PADA SAMSAT UPT PANGURURAN - Eva Malina Simatupang (JURNAL AKUNTANSI BARELANG, 2022)
This research is entitled "Effectiveness of Motor Vehicle Tax Collection in the Context of Increasing Regional Tax Revenue at SAMSAT UPT Pangururan 2015/2020 Period". The method used in this research is a qualitative description method. The purpose of this research is to analyze whether the implementation of Motor Vehicle Tax collection carried out by SAMSAT UPT Pangururan has been effective in increasing regional tax revenues and what obstacles and efforts are faced in increasing Motor Vehicle Tax receipts. The results of this study indicate that the receipt of Vehicle Taxes in Samosir Regency in 2015-2020 has been very effective in increasing Regional Taxes. This shows that the SAMSAT UPT Pangururan has worked well in managing the receipt of Motor Vehicle Tax, However, SAMSAT UPT Pangururan has not been serious in optimizing its tax revenue potential. The efforts made by SAMSAT UPT Pangururan have been able to increase the amount of Motor Vehicle Tax receipts. Although in 2019 and 2020 there were several obstacles that resulted in a decrease in the amount of Motor Vehicle Tax receipts